Optimization of Automotive Industry’s Manufacturing Process with Lean Tools - Nyárádi, Anita; Kocsi, Balázs; Tornyos, I.; Budai, István (International Journal of Engineering and Management Sciences, 2016)
Lean plays i mportant role in industrial environment. Automotive industries use lean tools in order to reduce cost and i mprove productivity. To achieve the company's objectives and so lve the detected problems I also used lean tools. By using lean tools we want to decrease total process cost (TPC). In order to achieve this target, the three-shift production has to reduce in two-shift production, which result decrease in the human resource costs and production costs. In order to reduce shifts we have to increase overall equipment efficiency (OEE) and eliminate minimum 50% of wastes by implementing 5s methodology, using Poka-yoke and scheduled maintenance.